Perwujudan Konsep On Pada Tokoh Frieren dan Heiter Dalam Anime Sousou No Frieren Karya Kanehito Yamada - Indriani, Emilia Fortuna; Santoso, Budi (KIRYOKU, 2024)
This study is intended to determine how the embodiment of the value of on, gimu, and giri in the characters Frieren and Heiter in the anime Sousou no Frieren by Kanehito Yamada. The author uses descriptive qualitative method. This research design uses literary anthropology, which leads to literary text research that examines literary reflections as cultural reflections.  The data source was taken from Muse Indonesia's Youtube channel video entitled "Frieren: Beyond Journey's End" on episode 1-2. Frieren receives more on, giri, and gimu than Heiter because Frieren does not understand the concept of gratitude. She has a cold personality and lacks the ability to understand how quickly time passes for humans. After understanding the concept, Frieren tried to repay the debt of gratitude she had not been able to do. Frieren is able to pay his debt or giri in a timely manner. Heiter understood the concept of on so he did not carry as much of the burden of the values of on, giri and gimu as Frieren. Frieren and Heiter both carried the gimu ko to Himmel. Heiter managed to complete his gimu because he really took care of Fern until the end of his life. Frieren, on the other hand, had done her gimu and continued her gimu as part of her life principles. It can be concluded through this anime, Japan still maintains the moral concepts of on, giri and gimu.